rBC2LCN lectin as a potential probe of early‐stage HER2‐positive breast carcinoma - Shuuji Mawaribuchi; Yoshikazu Haramoto; Hiroaki Tateno; Yasuko Onuma; Yasuhiko Aiki; Yuzuru Ito (FEBS Open Bio, 2020)
The recombinant N‐terminal domain of BC2L‐C lectin (rBC2LCN) is useful for detecting not only human pluripotent stem cells but also some cancers. However, the cancer types and stages that can be detected by rBC2LCN remain unclear. In this study, we identified the human breast carcinoma subtypes and stages that can be detected by rBC2LCN. Compared with rBC2LCN‐negative breast carcinoma cell lines, the rBC2LCN‐positive cells expressed higher levels of human epidermal growth factor receptor 2 (HER2) and epithelial marker genes. Importantly, rBC2LCN histochemical staining of human breast carcinoma tissues demonstrated the utility of rBC2LCN in detecting breast carcinoma types that express HER2 and have not spread much in the early phase of growth. We conclude that rBC2LCN may have potential as a detection probe and a drug delivery vehicle to identify and treat early‐stage HER2‐positive breast carcinoma.